2020
DOI: 10.3126/jkmc.v8i4.32381
|View full text |Cite
|
Sign up to set email alerts
|

Cat fit and bull fight: Assessment of aggression in medical students as a prelude to conduct violence in future

Abstract: Background: The intensity of aggression present in any person determines his/her threat to conduct violent and impulsive act against members of the society or else family, friends or foes, which necessitates a crucial analytical instrument for identification of such behaviour in smaller groups of societies. Objectives: To assess a group of medical students from Kathmandu, Nepal for potential risk they bear to conduct violence in future medical practice. Methodology: A self-administered pre-validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This finding was confirmed by a study conducted by Alradaydeh and Alorani (2017) (34) who reported that the major type of aggressive behavior among university students in Jordan was physical aggression, followed by hostility, anger, and verbal aggression. Moreover, Acharya, et al (2019) (40) , mentioned that physical aggression was the most prominent type of aggression among 235 university students from Nepal. In this respect, Bukhari et al (2017) (41) concluded that male was higher in anger and physical aggression, however, females exhibited higher verbal aggression and hostility.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was confirmed by a study conducted by Alradaydeh and Alorani (2017) (34) who reported that the major type of aggressive behavior among university students in Jordan was physical aggression, followed by hostility, anger, and verbal aggression. Moreover, Acharya, et al (2019) (40) , mentioned that physical aggression was the most prominent type of aggression among 235 university students from Nepal. In this respect, Bukhari et al (2017) (41) concluded that male was higher in anger and physical aggression, however, females exhibited higher verbal aggression and hostility.…”
Section: Discussionmentioning
confidence: 99%